“Need to Communicate the right Paradigm” in Educational System. A Study on the Educational System for the Hearing Impaired in Schools in the State of Kerala - Manjith, Mohan (2006)
The aim of this dissertation is to illustrate that through the method of qualitative interviewing, it is possible to bring out a clear and effective study of the educational system/s being followed for the hearing impaired in the State of Kerala, with special emphasis given to the Capital city of Trivandrum. The dissertation employs a method of qualitative semi-structured interviewing wherein one of the levers “Education Department” (Ainskow, 2004) of change is studied in depth and an effort being made to analyze the flaws in the system/s under practice. Also an effort is being made to dig out the root cause underpinning the chances of existence of flaws in the educational system as a whole. The research is initiated through a pilot study, which helped me understand the ground realities on both the subject under consideration and also on the methodology and this helped me to carry out my research effectively and efficiently. Qualitative interviewing, wherein semi-structured interviews formed most of the methodology part, was supported by secondary data from resources. Interviews of 7 officials who held high rankings in institutions that were responsible for education of the hearing impaired in the State of Kerala were taken over the limited time span. The interviews were transcribed personally, stored and then interpreted to draw out some major analysis. The manner in which the interviews were analyzed and interpreted helped me achieve answers to my research question; which was mainly focusing on analyzing the flaws in the educational system for hearing impaired. Further deep down studies revealed that communication gap and peoples perception on paradigms were the root causes behind the existence of flaws in the system of education. Finally I drew some conclusion regarding my research contribution.